Gereja Dalam Pusaran Digitalisasi Dan Humanisasi - Arly E. M. de Haan; Rolin F. S. Taneo (Sekolah Tinggi Teologi Ekumene Jakarta., 2023)
There are at least three major realities that should be highlighted when entering the 21st century, including digitalization that is growing rapidly, humanization that is starting to be intensified, and the intensity of religion fortifying its people in warding off the dangers of technological progress and humanization that has the potential to damage the lives of religious people. Digitalization creates an opium for humans while humanization gives birth to the understanding that humans can live without God. For this, religion must be able to be a filter for the spread of digitalization and humanization and contribute to real contributions. In its development, there are obstacles that the church encountered when it began to try to instill critical values on these two phenomena. The church was later accused of being an institution that restrained its congregation. Consider Nietzsche's thesis that he fought persistently to convince religious people that man occupies a position above religion and all forms of understanding that make human space limited. Man must become a complete man, transcending all existing orders. The term Nietzsche used was Ubermensch. This becomes a serious problem if not addressed wisely. Not after Nietzsche criticized the church, Yuval Harari appeared and confirmed the humanist position but with a note that there must be artificial intelligence that helps humans. Technology is glorified. This is where both Nietzsche and Harari come to a contrasting understanding. After all of the above is mentioned, then using the literature method, this article offers a solution that the church should be present to navigate the direction of technology and humanism. Faced with the rapid development of technology, the church stresses the need for responsible and ethical use of technology.